PENGARUH COGNITIVE RESTRUCTURING UNTUK MENGURANGI SOCIAL ANXIETY MELALUI BIMBINGAN KELOMPOK DI SMP NEGERI 25 PEKANBARU - Helmida Yani; Rosmawati Rosmawati; Roby Maiva Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Social anxiety is where a person feels anxious about things that are new or related to a new environment, problems experienced by group members such as difficult to adapt to the new environment and new friends feel that they are not ready to eliminate the anxiety felt so they often think negatively compared to positive thinking. This study aimed to determine social anxiety before and after cognitive restructuringwas applied through group guidance and to determine the effect of cognitive restructuring through group guidance to reduce social anxiety. The study was conducted in Pekanbaru State Junior High School 25 of eight subjects with purposive sampling technique. The research design was pre-experiment with the one group pretest post-test model. The instrument of data collection used is a social anxiety questionnaire adapted from W. Ray Crozier (2001). The results showed that there were differences in social anxiety before and after cognitive restructuring was given with asignificant value of 0.012 <0.05. In addition, based on the Spearman rank test it is known that there is a significant effect between cognitive restructuring on social anxiety students with a significance value of 0.001 <0.05. The influence of cognitive restructuring techniques to reduce social anxiety 12.5% while 87.5% is low is influenced by other factors originating in and from the environment. From the resultsthat can continue to carry out activities that are able to reduce students' social anxiety towards the environment to be able to reduce the feeling of social anxiety can change the negative mindset to be positive towards the surrounding environment by using cognitive restructuring techniques.Key Words : Cognitive Restructuring, Social Anxiety, Group Guidance